Cross-country distribution dynamics of carbon emissions and intensity: Before and after the global financial crisis - Wei, Yigang; Wojewódzki, Michał; Cheong, Tsun Se; Shi, Xunpeng (Review of Economic Analysis, 2024)
This study aims to explore the levels of regional disparity in carbon emissions and intensity among different countries. Our study employs the distribution dynamics approach to uncover transition probabilities and the long-term evolution of relative per capita carbon emissions (REPC) and relative carbon intensity (REPGDP) across 204 countries. We split the analysis period into pre-crisis (2000-2007) and post-crisis (2007-2016) and divided countries into four income groups. The results indicate the emergence of new convergence clubs post-crisis in both REPC and REPGDP. Furthermore, the majority (many) of the low- (high) income countries congregate to extremely low (above the global average) REPC levels in the long run. Finally, using mobility probability plots, we identify low-(high-) income countries with REPC (REPGDP) levels of 2.3 (3.8) times the global average to have the highest probabilities of around 100 (65) per cent of diverging further above the worldwide average in the coming years. The study expands knowledge about convergence-divergence patterns in carbon emissions and intensity, which is crucial for energy management and effective climate policies. Moreover, it can aid in climate change projections and promote a fairer climate framework, encouraging high-emission countries to take greater responsibility.